KEBUTUHAN AKTUALISASI DIRI SISWA KELAS AKHIR: STUDI KASUS SISWA KELAS XII SMA ANNUQAYAH GULUKGULUK SUMENEP - Moh. Ridwan (Living Sufism: Journal of Sufism and Psychotherapy, 2022)
Self-actualization of final grade students is a process that students do to achieve completed self-realization. Self-actualization occurs when individuals have a conformity with the environment that supports them to grow and develop. Self-actualization is very influential in a life because it helps achieve many things, including self-optimization in an environment. Some final year students at Annuqayah High School are known to have been able to actualize themselves even though the school has been known for its uncompromising education system. It is interesting to know more about the self-actualization needs of the final grade students and their efforts to actualize themselves considering the location of the school which is also under the auspices of the Annuqayah Islamic Boarding School.The purpose of this study is to reveal and get an overview of the self-actualization needs of final grade students of SMA Annuqayah in the academic year 2021/2022 and their efforts with Carl R. Rogers’self-actualization theory approach. This research is a qualitative research conducted by means of a case study. To obtain data, researchers conducted in-depth interviews, observations, and documentation. The subjects, hereinafter referred to as informants, consisted of 2 final grade students on the recommendation of the school leadership and the guidance & counseling (BK) teacher.The results of this study indicate that to achieve self-actualization students need several things, among others; a, the need for self-awareness, potential, and desires., b, the need for awareness of their experiences., c, the need for a positive response from outside themselves. While the efforts made to achieve self-actualization include; a, open up to every situation. b, live independently and full ofcreativity.